(untitled) (Intent Research Scientific Journal, 2023)
Ethnography is a vivid example of national exoticism. They can also be called exotic lexicon. The Uzbek language is rich in ethnographies. This is due to the fact that they live in different regions and have cultural ties with different peoples.